N-doped carbon sheets arrays embedded with CoP nanoparticles as high-performance cathode for Li-S batteries via triple synergistic effects - Xiao, Kuikui (2022)
Cycle stability and rate performance are the key factors for the commercial applications of Li-sulfur batteries. Herein, N-doped carbon sheets with cobalt compounds nanoparticles anchored on carbon cloth (CoP/NC or Co9S8/NC) are synthesized to act as sulfur host in Li-S batteries. The porous 2D N-doped carbon sheets uniformly grow on the surface of carbon cloth to form open porous structure, providing a mechanically robust space for the deposition of sulfur species and offering direct channels for fast Li+ diffusion. The cobalt compounds, serving as adsorbent to alleviate the shuttle effect of polysulfides by providing strong affinity and to accelerate the redox kinetics via their electrocatalytic effect toward the polysulfides conversion, are firmly and evenly embedded in the carbon sheets. Through comparison, the higher electrocatalytic effect of CoP/NC than Co9S8/NC are proved by the cyclic voltammetry (CV) of the symmetric cell with Li2S6 electrolyte as both negative and positive electrodes. Benefiting from the unique open structure, proper adsorption ability and superior catalytic effect of CoP/NC, it shows enhanced electrochemical performance, delivering high specific of 1482 mAh g−1 at 0.1C and 678 mAh g−1 at 3C and outstanding cycling performance with capacity decay of only 0.0327% per cycle for over 560 cycles.